Clinical profile and predictors of outcome in congenital duodenal obstruction - Chandrasekaran, Sankkarabarathi; Asokaraju, Anirudhan (International Surgery Journal, 2017)
Background: Congenital duodenal obstruction is a broad term that refers to a variety of disorders like duodenal atresia, duodenal stenosis, annular pancreas, duodenal membrane and preduodenal portal vein. The aim of this study was to analyse in detail the entire clinical profile of duodenal obstruction and to study the short-term outcome. Methods: A prospective descriptive study was conducted in the Department of Paediatric Surgery, Institute of child Health and Hospital for Children, Egmore, Chennai, among all babies with suspected duodenal obstruction based on clinical symptoms and subsequently proven by surgery from September 2013 to January 2015. Fifty babies were selected for this study based on the eligibity criteria. Results: Upper gastrointestinal contrast radiography is the gold standard investigation in diagnosing duodenal membrane with a hole. The type of surgery such as the duodenoplasty, duodenoduodenostomy or duodenojejunal anastomosis did not affect the post-op outcome. Conclusions: Long term follow up is warranted to know the actual incidence of requirement for redo procedure for feed intolerance. The presence of coexisting Down’s syndrome and congenital cardiac lesions increases the mortality rate in these children.